"E.T.A. Hoffmann's Romantic Tale 'Der Sandmann' or The Pathology of a Migraine". Issue 3 (5th March 2013) - Spreizer, Christa
Abstract: Much critical literature on E.T.A. Hoffmann's tale "Der Sandmann" centers around whether the young physics student Nathanael is suffering from some neurotic, psychological malady due to a childhood trauma, or whether a series of supernatural events have targeted him to lead a tortuous and ultimately tortured existence at the hands of the monstrous Coppelius, aka The Sandman. Other scholars analyze this Romantic tale as a reaction to an historical present rather than within abstract or strictly psychoanalytic principles, more specifically, the influence of Bamberg, a center of medical and psychiatric research and practice, on Hoffmann's works. I wish to continue this line of inquiry by looking at the tale from a more modern medical perspective: Nathanael's bouts of madness may have a physical or neurological rather than purely psychological basis which would have gone unnoticed during the early 1800s. I believe Hoffmann's intricate narrative on Romantic conceptions of the artist, society, sickness and healing, outlines the pathology of a patient suffering from a variety of symptoms associated with "migraine with aura.""Der Sandmann" should be included among works exhibiting descriptive evidence of migraine experience. This would provide a new contextual orientation for the tale and also further illustrate the progress and limitations of Romantic era psychiatric practices in its confrontations with reason, unreason, and madness.